Landslide Soil Failure Parameters Characterization Using Geoelectrical Resistivity Methods in Uruagu, Nnewi, Anambra State, Nigeria - Charles Chinedu Uwaezuoke; Osariere John Airen (European Scientific Journal, ESJ, 2023)
Electrical Resistivity Imaging (ERI) and Vertical Electrical Sounding (VES) were deployed over the Uruagu landslide area. The main purpose of the study was to characterize the landslide failure parameters in to identify the soil failure mechanisms. Ten profiles of 2D ERI measuring 200 m each, and thirty VES, with three VES along each profile, were executed. Nine of the ten profiles were executed within the landslide site while one profile was executed in a residential street as a control profile. Four soil samples were also taken for physical and geotechnical laboratory index analysis. The PASI resistivity meter was used for the geoelectrical resistivity measurements. The Wenner-Schlumberger array was deployed for the ERI with a minimum electrode spacing of 10 m. The Schlumberger array was deployed for the VES  with a maximum current spacing of 130 m. ERI resistivity data analysis involved inversion using the RES2DINV software package involving mean model residual and construction of iso-apparent resistivity contour maps. VES resistivity data analysis involved calculated parameters from plotted field data on a log-log graph then used as initial models in an iterative forward modeling WinResist software package. The results of the ERI and VES for the control profile reveal that the subsurface strata are originally composed of silty clay of resistivity values (16.7 – 60.9) Ωm, clayey silty sand having resistivity values (116 – 800) Ωm and sandstone layer with resistivity values (>814 Ωm). The ERI and VES results for the devastated landslide site reveal counteraction material of resistivity values (>814 Ωm), colluvia and regoliths (116 - 300 Ωm), and variably wet weathered sandstones of resistivity values (<60.9 Ωm). The laboratory results revealed the landslide site is majorly composed of silty sandy clay, silty clay, sandy silty clay, and sandstones as the pre-landslide existing lithologies. The natural water content ranges from 10.6% to 14.0%. The liquid limit ranges from 44.0% to 46.0%, the plastic limit ranges from 15.0% to 17.0%, and the plasticity index from 28.0% to 29.1%. The geophysical and laboratory results revealed consistency in the lithological units in agreement with the characteristic geology of the study area. The landslide site has high gully slope gradients and collects a large volume of floods during the intense rainy season. These soils, during the intense rainfall, imbibe more water, following their high plasticity slide along the sandstone to activate the soil failure.